Chaotics and the post-digital in Ciarán Carson's Exchange Place. Issue 7 (10th November 2017) - Barrios-O'Neill, Danielle
ABSTRACT: A variety of critics and theorists have since demonstrated how approximations of chaotic principles occur in literary systems and texts. Across disciplines, this set of approaches has emerged concurrently with the arrival of increasingly powerful computing technologies. This paper examines the novel Exchange Place by Ciaran Carson, applying Katherine Hayles's concept of 'chaotics' to the text to read for established chaotic features including unpredictability, complex forms, nonlinear relationships and multi-scalar representations. Foregrounding interactions between chaotics as proposed in the 1990s and contemporary post-digital environments, I highlight three distinguishing elements of Exchange Place, which are explained and illustrated through close reading, that reflect an evolving, twenty-first-century chaotics; I have termed these pulsating subjectivity, mercurial body-text and collective mind. Crucial to this discussion are evolutions in subjectivity in the post-digital age, where bodies and texts have become deeply embedded with, and within, high-tech communication networks. The result is a new horizon of textual strategies and effects that privilege network-ecologies of personhood over individuality and coherence; Exchange Place is a quintessential illustration of this literary horizon.